Comparative Clinical Evaluation of Traditional and Electronic Yoni Dhupana Using Saraladi Yoga in the Management of Yonigata Lakshanas: A Dual Case Study - Dr. Asha K P,; Prof. Manjusha Karkare,; Dr. Saurabh Agrawal,; Dr. Priyanka Gaikwad, (The Bioscan, 2025)
Background: Yoni Vyapad in Ayurvedic literature encompasses a range of gynecological conditions characterized by white vaginal discharge, vulval itching, dyspareunia, and inflammation, adversely affecting women's quality of life. Yoni Dhupana, a traditional fumigation therapy using herbal formulations like Saraladi Yoga, is a proven modality in Ayurvedic practice. However, traditional fumigation methods lack standardization and pose challenges in clinical reproducibility. Objectives: To compare the clinical efficacy and therapeutic outcomes of traditional Yoni Dhupana and Yoni Dhupana using an innovative Electronic Dhupana Yantra in two patients presenting with similar Yonigata Lakshanas. Methods: This dual case study was conducted at the Department of Prasuti Tantra & Stree Roga, Sanjeevani Hospital, Jodhpur. Two female patients with comparable Yonigata Lakshanas were selected. Patient 1 received traditional Yoni Dhupana using cow dung cakes and Saraladi Yoga, while Patient 2 underwent the same procedure through an electronic Dhupana Yantra, developed as part of a doctoral research project. Both treatments were administered once daily for 7 days. Clinical assessments were recorded pre- and post-intervention, and outcomes were compared. Results: Both patients showed significant symptomatic improvement. The patient treated with the electronic Dhupana Yantra demonstrated complete resolution of symptoms including vulval itching, burning sensation, white discharge, dyspareunia, and cervical congestion. The traditionally treated patient exhibited partial relief, with minor residual symptoms like mild discharge and burning. No adverse effects were observed in either case. Discussion: While both modalities were effective, the electronic method yielded superior and consistent outcomes, likely due to controlled heat, standardized dhupa concentration, and improved patient comfort. This suggests a potential role for technological integration in enhancing traditional Ayurvedic therapies without compromising their classical foundation. Conclusion: Yoni Dhupana is effective for treating Yonigata Lakshanas, and the electronic Dhupana Yantra offers enhanced clinical efficacy and procedural standardization. Further controlled trials are recommended to validate these findings and support broader clinical adoption of device-assisted Ayurvedic interventions.